Students’ knowledge in the waqf land concept / Siti Nadiah Mohd Ali ... [et al.] - Siti Nadiah, Mohd Ali; Rashidah Paujah, Ismail; Abd. Halim, Mohd Noor; Nurul Sahida, Fauzi; Nor Nazihah, Chuweni; Farhan, Md Dahlan (2015)
Waqf is an endowment made by a Muslim for religious, educational, or other charitable causes. To promote thewaqf concept amongst Muslims, we investigated students’ knowledge at the university level. In the earlier stages, it should start from the educational system which is near to the students. Muslims may not realise this waqf concept if they are not aware of or don’t want to know about it. Since Real Estate Management programmes have a significant relationship with waqf, the purpose of this paper is to investigate the level of knowledge in the waqf land concept by Muslim students who have studied Real Estate Management. It has been focused on endowment made by the Muslims and potential career opportunities for Real Estate Management students in waqf management in Malaysia. This study has been limited amongst undergraduates of Universiti Teknologi MARA Perak who studied Real Estate Management in the District of Perak Tengah. The quantitative method has been used in the data collection and analysis of this study. Structured questionnaires were distributed amongst students in the universitiy. Data from the questionnaires were analysed using the IBM SPSS software. The result findings indicated that the level of knowledge on the waqf concept amongst Real Estate Management university students is good. The result of this study did not show any significant difference in the knowledge in the waqf land concept between male and female students and there was no significant difference in the level of knowledge amongst students from different levels of CGPA. Therefore, this paper will propose to the Department of Estate Management to take into consideration to include waqf development as one of the major syllabus subjects in their programme in order to make sure the knowledge and practical development amongst Muslim students after graduations can benefit waqf performances in Malaysia, efficiently.